2012
DOI: 10.3109/07357907.2011.629379
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylceramide Synthase Protects Glioblastoma Cells Against Autophagic and Apoptotic Death Induced by Temozolomide and Paclitaxel

Abstract: Glioblastoma is a deadly cancer with intrinsic chemoresistance. Understanding this property will aid in therapy. Glucosylceramide synthase (GCS) is associated with resistance and poor outcome; little is known about glioblastomas. In glioblastoma cells, temozolomide and paclitaxel induce ceramide increase, which in turn promotes cytotoxicity. In drug-resistant cells, both drugs are unable to accumulate ceramide, increased expression and activity of GCS is present, and its inhibitors hinder resistance. Resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 46 publications
4
33
0
Order By: Relevance
“…Giussani and coworkers showed that glucosylceramide protects glioblastoma cells against autophagic and apoptotic by Temozolomide and Paclitaxel induced death, and the concomitant use of inhibitors of glucosylceramide synthase revert that resistance to enhance the cytotoxic effects of these drugs [7]. These two reports are consistent with experimental data MiaPaca-2 cell line.…”
Section: Discussionsupporting
confidence: 61%
“…Giussani and coworkers showed that glucosylceramide protects glioblastoma cells against autophagic and apoptotic by Temozolomide and Paclitaxel induced death, and the concomitant use of inhibitors of glucosylceramide synthase revert that resistance to enhance the cytotoxic effects of these drugs [7]. These two reports are consistent with experimental data MiaPaca-2 cell line.…”
Section: Discussionsupporting
confidence: 61%
“…SphK1, S1P and its receptors play a vital role in induction of cancer chemoresistance. Selection of TMZ-resistant GBM cells has been shown to be associated not only with an increase in GlcCer synthase [ 138 ], but also with SphK1 expression [ 149 ]. However, in spite of GSC inhibition hindering resistance to TMZ-induced autophagic death [ 138 ], SphK1 down-regulation was found to have a similar proapoptotic effect on TMZ-sensitive and -resistant cells [ 149 ].…”
Section: Sphingolipids In Gbm Cell Survival and Death Resistancementioning
confidence: 88%
“…Interestingly, enhanced lethality correlated with increased autophagy that was dependent on the expression of CerS6. In addition, exposure of human GBM cells to TMZ promoted autophagic cell death by the production of ceramide [ 138 ].…”
Section: Ceramide In Necrotic and Autophagic Death Of Gbm Cellsmentioning
confidence: 99%
See 2 more Smart Citations